Bioethanol production from woody stem Prosopis juliflora using thermo tolerant yeast Kluyveromyces marxianus and its kinetics studies. (December 2019) - Sivarathnakumar, S.; Jayamuthunagai, J.; Baskar, G.; Praveenkumar, R.; Selvakumari, I. Aberna Ebenezer; Bharathiraja, B.
Highlights: Bioethanol production using Kluyveromyces marxianus from Prosopis juliflora was investigated. Combined pre treatment of auto-hydrolysis coupled with acid hydrolysis was done to enhance the sugar yield. The maximum concentration of 21.45 g/l of bioethanol was obtained at optimal conditions. The product and biomass yield coefficients were found to be 0.67 g/g and 0.28 g/g. Modified Gompertz model show appreciable agreement between simulated and experimental values. Abstract: In the present study, Kluyveromyces marxianus was utilized to study the batch fermentation kinetics of biomass production, substrate utilization and bioethanol production from woody stem Prosopis juliflora . The pre-treated substrate was subjected to Simultaneous Saccharification and Fermentation (SSF) under optimised conditions of pH (4.9), temperature (41 °C), substrate concentration 5% (w/v), inoculum concentration 3% (v/v) and the maximum concentration of bioethanol was found to be 21.45 g/l. The experimental data thus obtained from cell growth, substrate utilization and product formation are employed in the determination of kinetic parameters. Biological models such as Logistic model, Hinshelwood model were used for microbial growth and substrate utilization kinetics respectively. In case of product kinetics, Leudking-Piret plot, Gompertz model and Modified Gompertz model were utilised. Based on these models, kinetic parameters like maximum specific growth rate (µm), saturation constant (Ks), growth associated (α), non-growth associated (β) and yield coefficients (YX/S, YP/S ) were estimated.